2021
DOI: 10.1111/bcp.14758
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among genetic polymorphism of SLCO1B1, rifampicin exposure and clinical outcomes in patients with active pulmonary tuberculosis

Abstract: Aims: Rifampicin is a key drug for the treatment of tuberculosis (TB). Little is known for the relationship between the rifampicin pharmacokinetics and genetic polymorphisms in the Asian population. We aimed to investigate relationship between genetic polymorphism of SLCO1B1 and rifampicin exposure and its impact on clinical outcomes in Korean patients with active pulmonary TB.Methods: From February 2016 to December 2019, patients with active pulmonary TB who were taking rifampicin for >1 week were prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“… 32 Similarly, Chigutsa et al reported high allelic frequency of the SLCO1B1 rs4149032 polymorphism and 28% reductions in the bioavailability of rifampin for homozygous variants. 40 No statistically significant increase in the rifampicin exposure for the homozygous TT of g.38664 C > T (rs4149032) was observed in the study of Kim et al 37 However, the large number of studies reviewed here did not report any observed significant effect of SLCO1B1 rs4149032 SNP polymorphism with rifamycin pharmacokinetic variation.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“… 32 Similarly, Chigutsa et al reported high allelic frequency of the SLCO1B1 rs4149032 polymorphism and 28% reductions in the bioavailability of rifampin for homozygous variants. 40 No statistically significant increase in the rifampicin exposure for the homozygous TT of g.38664 C > T (rs4149032) was observed in the study of Kim et al 37 However, the large number of studies reviewed here did not report any observed significant effect of SLCO1B1 rs4149032 SNP polymorphism with rifamycin pharmacokinetic variation.…”
Section: Resultsmentioning
confidence: 61%
“… Patients heterozygous and mutant homozygous for rs4149032 had 18% and 28% reductions in the bioavailability of rifampicin respectively. ABCB 1 rs1045642 rs2032582 rs1128503 rs3842 The ABCB1 G2677T (rs2032582) showed no statistically significant increase (19%) in the CL/F and a 19% increase in the mean transit time [ 41 ] SLCO1B1 rs2306283 rs4149032 162 pulmonary tuberculosis from two clinical studies receiving rifapentine in South Africa No effect on oral clearance, apparent volume of distribution, and F was detected [ 37 ] SLCO1B1 rs2306283 rs11045819 rs4149056 rs4149032 105 adult patients were newly diagnosed with active pulmonary TB, and Twenty (19%) patients had diabetes mellitus rs4149032 wild type (TT) had lower oral clearance and higher AUC but no statistically significant differences were detected [ 35 ] SLCO1B1 rs4149032 rs2306283 A cohort of 50 HIV negative patients 25 with rifampicin sensitive pulmonary TB and 25 patients with rifampicin-resistant When adjusted for all covariates no significant effect of the two SLCO1B1 genotypes on rifampicin pharmacokinetics parameters was identified [ 36 ] SLCO1B1 rs11045819 rs4149056 rs59502379 rs2306283 rs4149015 72 TB patients (37 from Africa and 35 from the United States and Spain) and 16 healthy controls from USA Patients with the SLCO1B1 c.463C>A (rs11045819) polymorphism had 42% lower rifampicin AUC0–24, 34% lower Cmax, and 63% CL/F [ 44 ] SLCO1B1 rs2239751 rs2306283 rs11045819 rs4149014 rs4149032 rs4149056 173 adults of different races and countries of origin of which 12 are HIV positive None of the SLCO1B gene polymorphism investigated were associated with rifapentine exposure (AUC 24hour) Abbreviations ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies used high-performance liquid chromatography (HPLC) to determine the rifampicin concentration in plasma, 19,31,35,37,43,47,48 while five other studies applied liquid chromatography-mass spectroscopy (LC-MS/MS) with two detectors. 36,[38][39][40]42 In comparison, three studies used liquid chromatography-mass spectroscopy (LC-MS) 30,32,41,49 and one study used ultra-performance liquid chromatography (UPLC). 44 To develop the population PK model, the majority of the studies used NONMEM, except for three studies in which Monolix 19,46 and Phoenix NLME 36 were used.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Population PK/PD models are based on direct measurement of drug exposure or efficacy obtained from the patient, recognized as real-time MIPD (data-driven approach) [ 4 ]. Many population PK models have been established for various anti-TB drugs [ 10 , 23 , 61 , 94 ]. Apparently, many of these models are assembled on limited datasets and their applicability is confined to patients with similar characteristics as the base model, such as ethnicities or disease states.…”
Section: Future Perspectivesmentioning
confidence: 99%